Deformable liposomes as enhancer of caffeine penetration through human skin in a Franz diffusion cell test. (2nd October 2020) - Abd, E.; Gomes, J.; Sales, C. C.; Yousef, S.; Forouz, F.; Telaprolu, K. C.; Roberts, M. S.; Grice, J. E.; Lopes, P. S.; Leite‐Silva, V. R.; Andréo‐Filho, N.
Abstract: Objective: The permeation of hydrophilic molecules through the skin is still a challenge due to the barrier posed by stratum corneum, the outermost layer of the skin. Liposomes have frequently been used as carriers for different types of drugs and may also function as permeation enhancers. Propylene glycol has also been used as an edge activator in liposomes to increase the permeation. The aim of this work was to prepare liposomes containing an edge activator and loaded with caffeine to evaluate the potential of caffeine reaching the deeper layers in the skin. Methods: The formulations were prepared by a top‐down process using high‐pressure homogenization at 200 00 psi for 10 min. They were characterized by size, polydispersity index (PI), zeta potential (ZP), pH, caffeine content and encapsulation efficiency (EE%) on preparation (time zero) and after 30 days. Cytotoxicity of blank and loaded liposomes was assessed by MTT proliferation assay with a normal keratinocyte cell line (HaCaT). In vitro permeation tests were performed with human skin in Franz cells over 24 h, and caffeine concentration was determined in the skin surface, stratum corneum, dermo‐epidermal fraction and receptor medium by HPLC. Results: The caffeine liposomes with (DL‐Caf) or without propylene glycol (CL‐Caf) showed, respectively, mean size 94.5 and 95.4 nm, PI 0.48 and 0.42, ZP + 1.3 and + 18.1 mV and caffeine content of 78.57 and 80.13%. IC50 values of caffeine in DL‐Caf (3.59 v/v %) and CL‐Caf (3.65 v/v %) were not significantly different from conventional blank liposome (3.27 v/v %). The DL‐Caf formulation presented the best capability to enhance the caffeine permeation through the skin, resulting 1.94‐folds higher than caffeine solution. Furthermore, the caffeine flux from DL‐Caf was 1.56‐ and 3.05‐folds higher than caffeine solution and CL‐Caf, respectively. On the other hand, CL‐Caf showed the lowest caffeine penetration revealing the importance of edge activator to aid hydrophilic drug penetration to all skin layers. Conclusion: The DL‐Caf formulation tested was able to improve the permeation of caffeine through the stratum corneum and dermo‐epidermal layers, suggesting that this delivery system may be effective for deep skin delivery of hydrophilic drugs. Résumé: Objectif: La perm´eation de mol´ecules hydrophiles `a travers lapeau reste un d´efi en raison de la barri`ere oppos´ee par la couchecorn´ee, la couche la plus externe de la peau. Les liposomes ontfr´equemment ´et´e utilis´es comme supports pour diff´erents types dem´edicaments et peuvent ´egalement fonctionner comme des amplificateursde perm´eation. Le propyl`ene glycol a ´egalement ´et´e utilis´ecomme activateur dans les liposomes pour augmenter la perm´eation.Le but de ce travail ´etait de pr´eparer des liposomes contenantun activateur et charg´es de caf´eine pour ´evaluer le potentiel de lacaf´eine atteignant les couches les plus profondes de la peau. Méthodes: Les formulations sont pr´epar´ees par homog´en´eisationhaute pression `a 200 00 psi pendant 10 min. Elles sontcaract´eris´es par la taille des liposomes, l'indice de polydispersit´e(PI), le potentiel zˆeta (ZP), le pH, la teneur en caf´eine et l'efficacit´ed'encapsulation (EE%) `a la pr´eparation (temps z´ero) et apr`es 30jours. La cytotoxicit´e des liposomes `a blanc et charg´es est ´evalu´eepar un test de prolif´eration MTT avec une lign´ee cellulaire de k´eratinocytesnormale (HaCaT). Des tests de perm´eation in vitro sontr´ealis´es avec de la peau humaine dans des cellules de Franz pendant24 h, et la concentration de caf´eine est d´etermin´ee `a la surfacede la peau, dans la couche corn´ee, la fraction dermo‐´epidermique et le milieu r´ecepteur par HPLC. Résultats: Les liposomes contenant de la caf´eine avec (DL‐Caf)ou sans propyl`ene glycol (CL‐Caf) pr´esentent respectivement unetaille moyenne de 94, 5 et 95, 4 nm, PI 0, 48 et 0, 42, ZP + 1, 3 et +18, 1 mV et une teneur en caf´eine de 78, 57 et 80, 13%. Les valeursIC50 de la caf´eine dans DL ‐ Caf (3, 59 %v/v) et CL ‐ Caf (3, 65 %v/v) ne sont pas significativement diff´erentes de celles du liposome `ablanc conventionnel (3, 27 %v/v). La formulation DL‐Caf est cellequi permet la meilleure perm´eation de la caf´eine, avec une quantit´ede caf´eine dans la peau 1, 94 fois plus ´elev´ee que la solution decaf´eine. De plus, le flux de caf´eine de DL‐Caf est 1, 56 et 3, 05 foisplus ´elev´e que la solution de caf´eine et CL‐Caf, respectivement.D'autre part, CL‐Caf montre la plus faible p´en´etration de caf´eine, r´ev´elant l'importance de l'activateur pour aider `a la p´en´etration dela mol´ecule hydrophile dans toutes les couches de la peau. Conclusion: La formulation DL‐Caf test´ee am´eliore la perm´eationde la caf´eine `a travers la couche corn´ee et les couches dermo‐´epidermiques, ce qui sugg`ere que ce syst`eme d'administration peutˆetre efficace pour l'administration cutan´ee profonde de mol´eculeshydrophiles.